The state of ocular arterial blood flow in active retinopathy of prematurity - I. G. Trifanenkova; A. V. Tereshchenko; E. V. Erokhina (Российский офтальмологический журнал)
Purpose: to study the state of blood flow in the ocular arteries of patients with various forms, stages and course types of active retinopathy of prematurity (ROP). Material and methods. Colour duplex scanning was performed by colour Doppler mapping and pulsed Doppler sonography for 55 premature babies (55 eyes) with active ROP and 8 premature babies (8 eyes) without ROP signs. The children’s gestation age was 25 to 32 weeks, and the body weight at birth was 680 to1760 g. Blood flow was examined in the ophthalmic artery (OA), the central retinal artery (CRA) and the medial and lateral posterior short ciliary arteries (PSCA). Results. The ophthalmic artery revealed no significant differences between the children with ROP and without ROP, except for a significant increase in the peak systolic velocity (Vsyst) in an unfavorable course of stage III of ROP. The development of aggressive posterior ROP is accompanied by a statistically insignificant decrease in blood flow velocity of OA. Hemodynamic parameters of CRA indicate an increase in peripheral vascular resistance in children with an unfavorable course of ROP. A significant increase of Vsyst in the posterior short ciliary arteries was revealed in children with an unfavorable course of stages I–III of ROP and Vsyst, and Vdiast (diastolic blood flow velocity) in children with aggressive posterior ROP as compared with children without ROP. A pronounced impact of the ROP course (favorable or unfavorable) on the Vsyst, Vdiast, and PI indicators in the posterior short ciliary arteries was revealed. The most informative hemodynamic parameters in predicting the course of active ROP are Vsyst and Vdiast values in the ophthalmic artery and Vsyst in the posterior short ciliary arteries. The least informative were the hemodynamic parameters of the central retinal artery. Conclusion. The assessment of hemodynamic changes in eye arteries may be used as an additional diagnostic criterion in the early diagnosis of ROP.